Characterization of macroevolutionary patterns of body size in Testudinata - Farina, Bruna de Mattos (2021)
Organisms, vertebrates or invertebrates, display an amazing variation of body size and shape. The explanation for that, however, has always been debated, and different hypotheses, including trends of body size and thermoregulation, were proposed to explain this variation. In this sense, Testudinata shows great disparity of body size, especially if its rich fossil record is accounted. In this study, I explore the body size evolution in turtles, analyzing which factors could influence the observed patterns, and the presence of longterm evolutionary trends (e.g., Cope\'s Rule). For this, I constructed and time-calibrated two supertrees, based on two independent phylogenetic hypotheses, and collected body size data, as well as habitat information and age for each sampled taxon. To analyze body size data through time, I performed linear regression between paleotemperature and body size, ancestral state reconstructions, and macroevolutionary models fitting. The results suggest there is no general pattern that explains body size evolution in the group; instead, different habitats and lineages show different patterns of body size variation. Whereas freshwater turtles display a homogenous body size variation through time, possibly related to the uneven environmental factors of these habitats, terrestrial and marine turtles show more pronounced variation. Terrestrial turtles body size is likely related to environmental conditions and island colonization, and that of sea turtles to their pelagic lifestyle, which allowed great dispersal. Even though a few groups seemed to show some trends of body size, the evolutionary models indicate the opposite.